2013
DOI: 10.1111/dote.12066
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal polyps in pediatric patients undergoing routine diagnostic upper gastrointestinal endoscopy: a multicenter study

Abstract: Esophageal polyps are uncommon findings in pediatric patients, and reports have been limited to case reports. Esophageal polyps have been previously ascribed to esophagitis secondary to gastroesophageal reflux, medications, infections and recurrent vomiting. They have been associated with underlying conditions such as hiatal hernia, Barrett's esophagus, eosinophilic esophagitis and Crohn's disease. Presenting complaints of children with esophageal polyps have included vomiting, dysphagia, hematemesis and abdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
8
0
2
Order By: Relevance
“…The optimal treatment strategy is still to be defined. While some anecdotal reports showed regression of polyps after a course of anti-secretory therapy such as proton pump inhibitors [5,18], others have not demonstrated regression [14,18,22]. The minimum duration of anti-secretory therapy for polyp regression has also not been established.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal treatment strategy is still to be defined. While some anecdotal reports showed regression of polyps after a course of anti-secretory therapy such as proton pump inhibitors [5,18], others have not demonstrated regression [14,18,22]. The minimum duration of anti-secretory therapy for polyp regression has also not been established.…”
Section: Discussionmentioning
confidence: 99%
“…4,8,12 In our series, we found 3 lesions, corresponding to an estimated frequency of 0.14%, which is consistent with some reports. 13 In all patients, the main indication for upper digestive endoscopy was vomiting associated with other complaints, such as pyrosis and epigastric pain. The first one was an inflammatory lesion that we ascribed to a gastroesophageal reflux disease according to patient's clinical history and endoscopic findings (grade A esophagitis).…”
Section: Discussionmentioning
confidence: 99%
“…13 In children, the clinical features of gastrointestinal polyps depends on location and number of lesions. Considering the rarity of these lesions, the management of this patients is an increasing challenge for pediatric gastroenterologists and usually involves a multidisciplinary approach, especially in children with polyposis syndromes or a family history of gastrointestinal polyps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, oesophageal polyps may be encountered but are distinctly uncommon; in a review of over 9000 upper GI endoscopies, only 13 were identified, being mainly inflammatory, followed by squamous papillomas and rare hamartomas, the majority affecting the gastro-oesophageal junction. 10 …”
Section: Familial Adenomatous Polyposis (Fap)mentioning
confidence: 99%